A more-Comers populAtion trEated with an ultrathin struts polimer-free Sirolimus stent: an Italian post-maRketing study (the CAESAR registry) - Tarantini, Giuseppe; Cardaioli, Francesco; De Iaco, Giuseppe; Tuccillo, Bernardino; De Angelis, Maria Carmen; Mauro, Ciro; Boccalatte, Marco; Trivisonno, Antonio; Ribichini, Flavio; Vadalà, Giuseppe; Caramanno, Giuseppe; Caruso, Marco; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction The use of contemporary drug-eluting stents (DES) has significantly improved outcomes of patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). However, concerns exist regarding the long-term proinflammatory effects of durable polymer coatings used in most DES, potentially leading to long-term adverse events. First-generation polymer-free stent technologies, such as sirolimus- and probucol-eluting stents (PF-SES), have shown an excellent safety and efficacy profile. The aim of this study was to evaluate the safety and efficacy of the new ultrathin Coroflex ISAR NEO PF-SES, in a more-comers PCI population. Methods The CAESAR (a more-Comers populAtion trEated with an ultrathin struts polimer-free Sirolimus stent: An Italian post-maRketing study) registry is a multicenter, prospective study conducted in Italy, enrolling more-comers CAD patients undergoing PCI with the Coroflex ISAR NEO stent. Patients with left main (LM) disease, cardiogenic shock (CS), or severely reduced left-ventricular ejection fraction (LVEF) were excluded. The primary endpoint was target-lesion revascularization (TLR) at 1 year. Results A total of 425 patients were enrolled at 13 centers (mean age 66.9 ± 11.6 years, Diabetes mellitus 29%, acute coronary syndrome 67%, chronic total occlusion 9%). Of these, 40.9% had multivessel disease (MVD) and in 3.3% cases, the target lesion was in-stent restenosis (ISR). Clinical device success was reached in 422 (99.6%) cases. At 1 year, only two (0.5%) subjects presented ischemia-driven TLR. The 1-year rates of target vessel revascularization and MACE were 0.5% and 5.1%, respectively. Major bleeding was observed in four (1.0%) patients. Conclusion In this multicenter, prospective registry, the use of a new ultrathin Coroflex ISAR NEO PF-SES in a more-comers PCI population showed good safety and efficacy at 1 year.